Comparison of the gut microbiota and untargeted gut tissue metabolome of Chinese mitten crabs (Eriocheir sinensis) with different shell colors - Zhu, Xiaochen; Zhao, Yingying; Sun, Na; Li, Changlei; Jiang, Qing; Zhang, Yazhao; Wei, Hua; Li, Yingdong; Hu, Qingbiao; Li, Xiaodong (Frontiers in Microbiology, 2023)
The Chinese mitten crab (Eriocheir sinensis) is a highly valued freshwater crustacean in China. While the natural shell color of E. sinensis is greenish brown (GH), we found a variety with a brownish-orange shell color (RH). Although RH is more expensive, it exhibits a lower molting frequency and growth rate compared with GH, which significantly reduces its yield and hinders large-scale farming. The growth and development of animals are closely related to their gut microbiota and gut tissue metabolic profiles. In this study, we compared the gut microbiome communities and metabolic profiles of juvenile RH and GH crabs using 16S rRNA gene sequencing and liquid chromatography‒mass spectrometry (LC‒MS), respectively. Our findings indicated that the intestinal microbial composition and metabolic characteristics of E. sinensis differed significantly between RH and GH. At the operational taxonomic unit (OTU) level, the α-diversity of the gut microbiota did not differ significantly between RH and GH, while the β-diversity of the RH gut microbiota was higher than that of the GH gut microbiota. At the species level, the richness of unclassified_c_Alphaproteobacteria was significantly higher in the GH group, while the RH group had a significantly higher richness of three low-abundance species, Flavobacteria bacterium BAL38, Paraburkholderia ferrariae, and uncultured_bacterium_g__Legionella. In the current study, 598 gut tissue metabolites were identified, and 159 metabolites were significantly different between GH and RH. The metabolite profile of RH was characteristic of a low level of most amino acids and lipid metabolites and a high level of several pigments compared with that of GH. These metabolites were enriched in 102 KEGG pathways. Four pathways, including 1) central carbon metabolism in cancer, 2) protein digestion and absorption, 3) alanine, aspartate and glutamate metabolism, and 4) aminoacyl-tRNA biosynthesis, were significantly enriched. The correlation analysis between metabolites and microbiotas indicated that most key differential metabolites were positively correlated with the abundance of Shewanella_sp_MR-7. This research provided a greater understanding of the physiological conditions of E. sinensis varieties with different shell colors by comparing the gut microbiota and gut tissue metabolome.